Analysis of Factors That Influence Students' Investment Intentions towards Retail Sukuk in Pekanbaru Riau - Desi Novera Danur; Nisful Laila; Fitria Nurma Sari (Universitas Ahmad Dahlan, 2023)
The development of sharia finance has experienced significant developments in the last decade, especially retail sukuk which is proclaimed to be an alternative sharia investment that directly contributes to funding state infrastructure. This research aims to investigate the determinants of investment intentions which are measured using several variables, including product knowledge, investment understanding and sharia compliance. In addition, this research analyzes how these three variables influence investment intentions with risk as a moderating variable. This research used primary data from 90 respondents who were students at Sultan Syarif Qasim University Riau and Muhammadiyah University Riau. The analytical test tool used is SmartPLS 3.0 with the SEM-PLS (Structural Equation Model – Partial Least Square) analysis method. The results of this research show that investment knowledge and sharia compliance have a significant effect on investment intentions. Furthermore, this research also reveals that investment knowledge has no effect on investment intentions in retail sukuk. Furthermore, the research results explain that the risk variable does not moderate investment understanding of investment intentions. Meanwhile, the risk variable moderates the relationship between sharia compliance and investment intentions. The results of this research emphasize that the government through sharia financial institutions and academics must prioritize increasing investment knowledge and sharia compliance in order to encourage retail sukuk investment intentions in Pekanbaru.